Pengaruh Faktor Keuangan dan Non Keuangan Terhadap Manajemen Pajak dengan Indikator Tarif Pajak Efektif - Siti Lailatul Hidayah; Trisni Suryarini (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
This study aims to analyze the effect of financial factor and non-financial factor on the tax management which proxied by effective tax rate. Financial factors is proxied by fixed asset intensity and inventory intensity, whereas non-financial factors is proxied by independent commissioners, taxation facilities and economic growth. The population in this study are consumer goods companies which listed in Indonesia Stock Exchange in 2014-2018. The sample selection uses the purposive sampling method and obtained 27 companies with 126 units of analysis. Data analysis methods that used in this research is multiple linear regression. The results showed that taxation facilities had a significant negative affect on tax management. Meanwhile, fixed asset intensity, inventory intensity, independent commissioners, and economic growth are not significantly affected tax management. The conclusions of this research are fixed asset intensity, inventory intensity, independent commissioners, and economic growth can not determine the decision of tax management in companies, then taxation facilities can determine the decision of tax management.